Sifat kimia dan organoleptik food bar kombinasi tepung mocaf (Modified cassava flour) dan tepung kacang tanah (Arachis hypogeaea L.): Chemical and organoleptic properties of foodbar mocaf flour (Modified cassava flour) And Peanut Flour (Arachis hypogaea L.) - Setyowati, Dewi Putri; Maghfiroh, Khoirin (TEKNOLOGI PANGAN : Media Informasi dan Komunikasi Ilmiah Teknologi Pertanian, 2024)
Food bars are made by combining a variety of mashed food ingredients. These ingredients are fortified with additional nutrients such as cereals, dried fruit, or nuts, which are then held together into a compact form with the help of binders. The aim of this study was to see how mocaf flour and peanut flour affected the chemical and organoleptic qualities of food bars. A one-factor completely randomised design (CRD) was utilised in this study. There were three amounts of mocaf flour and mung bean flour, namely 70g : 30g, 50g : 50g, 30g : 70g. The one-way ANOVA test was used to analyse chemical data, followed by the BNT test. Chemical analysis includes moisture content, ash content, and fiber content. Organoleptic data analysis using the hedonic test. The moisture content test revealed no differences (p=0.36), whereas there were differences in the ash content test (p=0.00), the fiber content test (p=0.00). Organoleptic test showed that there were differences in aroma (p=0.047), texture (p=0.028), taste (p=0.016) and color (p=0.00). According to the results of the effectiveness test, the most effective treatment was A2 with the following criteria: 12.61% moisture content, 1.82% ash content, 1.78% fiber content, and 3.19 aroma, 3.38 color, 3 taste, 42, texture 3.15.